Refinements of the Pin-Based Pointwise Energy Slowing-Down Method for Resonance Self-Shielding Calculation—I: Theory - Choi, Sooyoung; Kim, Wonkyeong; Lee, Deokjung (Frontiers in Energy Research, 2021)
The pin-based pointwise energy slowing-down method (PSM), which is a resonance self-shielding method, has been refined to treat with the nonuniformity of material compositions and temperature profile in the fuel pellet by calculating exact collision probability in radially the subdivided fuel pellet under the isolated system. PSM has generated collision probability table before solving the pointwise energy slowing-down equation. It is not exact if the fuel pellet has nonuniform material compositions or temperature profile in all the subdivided regions. In refined PSM-CPM, the pre-generated table are not required by directly calculating the collision probability in all the subdivided regions of fuel pellet while solving slowing-down equation. There are an advantage and a disadvantage for the method. The advantage is to exactly consider the nonuniformity of the material compositions and temperature profile in the fuel pellet. The disadvantage is longer computing time than PSM when the fuel pellet has more than five subdivided regions. However, in the practical use for UO2 pin-cells, it is still comparable for the computation time with PSM and the conventional equivalence theory methods. In this paper, using simple light-water reactor 17x17 FA problems with uniform material compositions and temperature profile, it is demonstrated that PSMs (PSM and PSM-CPM) exhibits consistent accuracy in calculating the multiplication factor and the pin power distribution with no compromise in the computation time. More detailed accuracy assessments with various test cases, including problems representing the nonuniformity, are presented in the accompanying paper.